Antinomy of One and Many in Bhartçhari’s Vākyapadīya - Desnitskaya, Evgeniya A. A. (Acta Orientalia Vilnensia, 2006)
St. Petersburg State UniversityBhartçhari’s Vākyapadīya (VP) is notorious for the multiplicity of the mutually exclusive doctrines expounded there, without any final solution. This paper aims to demonstrate that in the case of every controversial question discussed in VP, the variety of views on it can be reduced to a basic antinomy which serves as a kind of proposition for the problem under consideration. These antinomies are sometimes expressed explicitly but very often they are hidden in the text of VP. The fundamental dichotomy is the opposition between pluralism and monism, the origin of which in turn can be traced in the contradiction between the grammatical background andontological trends of Bhartçhari’s philosophy. The way in which Bhartçhari integrates these extremities into a total system is analyzed in this paper on the basis of some passages, dealing with a certain semantic problem, from the 1st and the 3rd kāõóas of VP. Attention is focused on the concept of activity and its role in Bhartçhari’s philosophical discourse.